Colour from the perspective of Hadith: an overview - Zainan Nazri, Mohd Khairul Nizam; Hamisan@Khair, Nur Saadah; Mohamed Yusoff, Adnan; Abd Razzak, Monika@Munirah; Zainan Nazri, Nurul Jannah; Mat Ishak, Mardiana (EDP Sciences, 2015)
Colour is mentioned a few times in the Prophetic Traditions, signifying its values and symbolic representation for the people. The Prophet PBUH highlighted the significance of certain colours by describing his preferred colours for his clothing and he also approved or discouraged the usage of certain colours. Among the colours that are specifically mentioned and found in the hadith are white, red, green, black and yellow. These colours give different connotations as they were used in the Prophet 19s attires during battles and other occasions; and some bring about specific understanding, as stated by the Prophet PBUH. Interestingly, the use of certain colours as found in the hadith corresponds to that mentioned in the Qur 19an. Thus, this paper will observe the discussion among Muhaddithin regarding to the topic of colours in terms of its definition, function, significance and impact on the human life. The variety of meaning and understanding of colours according to different perspectives and cultures will also be discussed. The implications of using specific colours psychologically and scientifically will also be exposed in order to discover the connection between colours in the Prophetic Traditions and in our contemporary life.